The Influence of Organizational Culture and Employee Engagement on Employees Performance at Telkom University, Indonesia - Aditya Fathur Rohman; Dian Indiyati; Astri Ghina (International Journal of Science and Society, 2021)
The performance of a college is very dependent on the performance of its employees. Therefore, Telkom University must pay attention to the factors that affect the performance of its employees, including organizational culture and employee engagement. This study aims to determine how the organizational culture at Telkom University, how Employee engagement and employee performance at Telkom University, and to test and analyze the influence of Organizational Culture and Employee Engagement on Employee Performance. The population in this study was 1247 permanent employees at Telkom University, obtained based on data from the Telkom University HR Directorate as of August 2020, the sampling technique used was Proportional Stratified Random Sampling by taking representatives from the Faculties and Directorates. Calculated using the Slovin formula, in order to obtain the number of respondents as many as 303 people. The data collection technique uses a questionnaire that has been tested for validity and reliability, while the data analysis technique uses multiple regression analysis. The results of this study indicate that the Organizational Culture at Telkom University is in the Strong category, Employee Engagement is in the High category, and the employee's performance is above the target. Furthermore, organizational culture and employee engagement have a positive and significant effect on the performance of Telkom University employees, either partially or simultaneously.